Conceptual design of a new experimental setup to simulate aircraft tyre spin-up dynamics - Mahjouri, Saeed; Shabani, Rasoul; Skote, Martin (Emerald, 2023)
The first touchdown moment of aircraft tyres on a runway is the critical phase where maximum of the vertical and horizontal ground loads is produced. Some valuable drop tests have been performed at Langley research centre to simulate the touchdown and the spin-up dynamics. However, a long impact basin and a huge power source to accelerate and decelerate the landing gear mechanism have been used. Based on a centrifugal mechanism, the purpose of this paper is to propose the conceptual design of a new experimental setup to simulate the spin-up dynamics. Design/methodology/approach A schematic view of the proposed mechanism is presented, and its components are introduced. Operating condition of the system and the test procedure are discussed in detail. Finally, tyre spin-up dynamics of Boeing 747 is considered as a case study, and operating condition of the system and the related test parameters are extracted. Findings It is shown that the aircraft tyre spin-up dynamics can be simulated in a limited laboratory space with low energy consumption. The proposed setup enables the approach velocity, sink rate and vertical ground load to be adjusted by low power actuators. Hence, the proposed mechanism can be used to simulate the tyre spin-up dynamics of different types of aircraft. Research limitations/implications It is important to note that more details of the setup, including the braking and actuating mechanisms together with their control procedures, should be clarified in practice. In addition, the curved path introduced as the runway will cause errors in the results. Hence, a compromise should be made between the tyre pressure, path curvature, the induced error and the cost of the experimental setup. Practical implications The proposed experimental setup could be constructed in a limited space and at a relatively low cost. Low power actuators are used in the proposed system. Hence, in addition to the performance tests, fatigue tests of the landing gear mechanism will also be possible. Originality/value Based on a centrifugal mechanism, the conceptual design of a new experimental setup is presented for simulating the tyre spin-up dynamics of aircraft. Considering that the drag load developed during tyre spin-up following initial touchdown is an important factor governing the design of the landing gear mechanism and aircraft structure, the authors hope this paper encourages engineers to continuously make efforts to increase the transparency of the touchdown process, enabling optimisation of landing gear design.
Keywords: aircraft landing; tyre spin-up dynamics; experimental setup; ground loads